2022
DOI: 10.13057/biodiv/d230641
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of invasive tree species Bellucia pentamera on plant diversity, microclimate and soil of secondary tropical forest in West Sumatra, Indonesia

Abstract: Abstract. Solfiyeni, Syamsuardi, Chairul, Mukhtar E. 2022. Impacts of invasive tree species Bellucia pentamera on plant diversity, microclimate and soil of secondary tropical forest in West Sumatra, Indonesia. Biodiversitas 23: 3135-3146. The invasion of alien species in a region can alter species diversity. Bellucia pentamera Naudin is considered an alien invasive plant that has spread from Mexico to tropical America, and it is now invading some areas in Indonesia, including the tropical forest of Sumatra. Ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…In Lembah Harau, five individuals of B. pentamera were observed along with 16 local tree species, while in KBT, seven individuals of B. pentamera were found alongside 13 local tree species. The number of species observed in this study aligns closely with the findings of Solfiyeni et al (2022a), who reported 23 plant species in locations dominated by B. pentamera in the conservation forest of PT. Kencana Sawit Indonesian.…”
Section: Vegetation Composition and Structuresupporting
confidence: 91%
See 2 more Smart Citations
“…In Lembah Harau, five individuals of B. pentamera were observed along with 16 local tree species, while in KBT, seven individuals of B. pentamera were found alongside 13 local tree species. The number of species observed in this study aligns closely with the findings of Solfiyeni et al (2022a), who reported 23 plant species in locations dominated by B. pentamera in the conservation forest of PT. Kencana Sawit Indonesian.…”
Section: Vegetation Composition and Structuresupporting
confidence: 91%
“…Invasive species like Bellucia pentamera prefer slightly shaded environments for germination, such as under the canopy of bushes or other plants, and exhibit rapid growth to compete for light with surrounding vegetation. A previous study of Solfiyeni et al (2022a) suggests that the habitat of B. pentamera to be typically at the forest edge or within forest gaps, where higher light intensity and temperature prevail.…”
Section: Vegetation Composition and Structurementioning
confidence: 96%
See 1 more Smart Citation
“…Nevertheless, literature has shown comparable effects of other invasive tree species on these local conditions as found in our study. For example, the invasive tree Bellucia pentamera invading forest ecosystems in Indonesia caused an increase in mean air temperature and phosphorus and nitrogen content, while reducing water content [24]. The invasion of Pinus mugo in alpine ecosystems of central Europe has a similar effect, where ecosystems invaded by P. mugo generated drier, shadier, and more nutrient-rich ecosystems compared with non-invaded alpine grasslands [4].…”
Section: Impact Of P Contorta Invasion On Microenvironmental Conditionsmentioning
confidence: 99%
“…Therefore, periodic monitoring becomes very important and should be conducted. Solfiyeni et al (2022) explained that B. pentamera is an introduced plant with negative impacts on biodiversity and microclimate in secondary forest areas in West Sumatra. The existence of a negative association between B. pentamera and surrounding plants is due to the allelopathic compounds possessed by this species which inhibit the growth of other species and make this species able to invade an area rapidly (Inayah and Solfiyeni 2021).…”
Section: Floristic Composition Diversity Conservation Status and Pote...mentioning
confidence: 99%